Joint hypermobility syndrome: A review for clinicians. (7th October 2014) - Pacey, Verity; Tofts, Louise; Wesley, Alison; Collins, Felicity; Singh‐Grewal, Davinder
Abstract The term 'joint hypermobility' describes synovial joints that move beyond a normal range of motion. 'Joint hypermobilty syndrome' may also be associated with significant symptoms and impaired quality of life. The purpose of this review is to help the generalist to recognise the condition, exclude significant alternative diagnoses and understand the multidisciplinary approach to management.